The nose of patients with unoperated palatoschisis - Hajniš, Karol; Figalová, Pavla (Anthropological Review, 1973)
After having observed 36 children with cleft palate, the author proceeds to verify theories concerning the formation of faces of this kind of patients. He also applies anthropometric methods and biometric elaborations.